Arctic games: an analytical framework for identifying options for sustainable natural resource governance. Issue 1 (2nd January 2016) - Cole, Scott G.; Kinell, Gerda; Söderqvist, Tore; Håkansson, Cecilia; Hasselström, Linus; Izmalkov, Sergei; Mikkelsen, Eirik; Noring, Maria; Sandberg, Audun; Sjöberg, Eric; Soutukorva, Åsa; Franzén, Frida; et al.
Abstract: Changes in the Arctic are fuelled by a variety of drivers, including global warming, economic growth, improved access to natural resources, technological advances and globalisation processes. Further, the region is characterised by a diverse set of international agreements, national legislations and common pool resources. This presents challenges for actors to suggest, evaluate and agree on sustainable development alternatives. We propose an analytical framework to better understand (1) the types of trade-offs associated with Arctic futures and (2) actors' incentives for strategic behaviour. In the framework, game theory illuminates incentives and strategies among actors, cost-benefit analysis and economic valuation of ecosystem services help identify socially desirable outcomes and institutional analysis provides insight on how governance structures can support or interfere with policy intervention. We apply the proposed framework by analysing possible oil development futures for Lofoten in Northern Norway. For example, institutional analysis and estimates of costs and benefits of reducing oil spill risk and their distribution among actors are used for discussing incentive structures, including the use of side payments as a mechanism to mitigate conflicting interests.